2000
DOI: 10.1007/s000110050574
|View full text |Cite
|
Sign up to set email alerts
|

Clinical consequences of mast cell heterogeneity

Abstract: The heterogeneous morphological, biochemical and functional characteristics of mast cells from different species and from different tissue sites in the same species have been described for over 30 years. Far from being mere histochemical or pharmacological curiosities these differences have far reaching implications for therapeutic practice. This review concentrates on two important areas affected by mast cell heterogeneity, those of adverse reactions to therapeutic agents and the efficacy of anti-allergy ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…The reduction in Akt phosphorylation observed in Ag-cross-linked mast cells lacking CCL7 suggests a role for autocrine CCL7 in mast cell function through activation of the PI3K/Akt pathway. Other investigators reported that CCL7 alone did not stimulate degranulation (51) or migration (52) of HMC-1 human mast cells or histamine release by mouse peritoneal mast cells (53); however, our studies focus on CCL7 in the presence of Ag, and mast cells from different tissues are known to have different responses (54).…”
Section: Discussionmentioning
confidence: 74%
“…The reduction in Akt phosphorylation observed in Ag-cross-linked mast cells lacking CCL7 suggests a role for autocrine CCL7 in mast cell function through activation of the PI3K/Akt pathway. Other investigators reported that CCL7 alone did not stimulate degranulation (51) or migration (52) of HMC-1 human mast cells or histamine release by mouse peritoneal mast cells (53); however, our studies focus on CCL7 in the presence of Ag, and mast cells from different tissues are known to have different responses (54).…”
Section: Discussionmentioning
confidence: 74%
“…7), we cannot exclude a minor contribution of TRPC1, although this protein is thought not to be an endogenous component of CRAC in RBL-2H3 cells (44). Also, given the phenotypic diversity of mast cells (67,68) and the possible variations in the combinations of Orai and TRPC family members, it is possible that such combinations may vary among different subtypes of mast cells.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, skin mast cells are sensitive to nonspecific activation by opioids. In contrast, mast cells of the heart, lung and gastrointestinal system as well as basophils are not sensitive to opioids (116,119,120). As a consequence, most of these reactions are not life-threatening and include pruritus, urticaria and mild hypotension but are frequently misinterpreted as drug allergy.…”
Section: Opioidsmentioning
confidence: 99%